Samoa : Debt Management Performance Assessment - World Bank (World Bank, Washington, DC, 2020)
This report presents the findings of the mission based on information available as on 28 January 2010. An executive summary and a summary of the indicative performance indicators are presented in section two. The country context and recent developments and reforms in the area of public financial management, which are important for the evaluation, are provided in section three. Section four explains each scoring in detail. Section six concludes and discusses potential next steps.